Drying characteristics and some quality parameters of whole jujube (Zizyphus jujuba Mill.) during hot air drying - Tepe, Begüm; Ekinci, Raci (Italian Journal of Food Science, 2021)
Drying kinetics, water-soluble vitamins, total phenolic content (TPC), antioxidant capacity (AC) of the jujube fruits dried at 50, 60, and 70°C, and degradation kinetics of the quality parameters were investigated. The models fitted to drying were determined as Page at 50 and 70°C, Parabolic at 60°C. Increment in the drying temperature increased the drying rate and decreased the drying time. Water-soluble vitamins, TPC, and AC were significantly reduced by the drying process. Degradation of water-soluble vitamins increased with the drying temperature, although TPC and AC were not significantly affected by temperature. Thermal degradations of quality parameters were fitted to first-order kinetic.